2021
DOI: 10.1371/journal.pone.0246278
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary advantages of turning points in human cooperative behaviour

Abstract: Cooperation is crucial to overcome some of the most pressing social challenges of our times, such as the spreading of infectious diseases, corruption and environmental conservation. Yet, how cooperation emerges and persists is still a puzzle for social scientists. Since human cooperation is individually costly, cooperative attitudes should have been eliminated by natural selection in favour of selfishness. Yet, cooperation is common in human societies, so there must be some features which make it evolutionaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…For instance, using data from the human connectome, Marinazzo and colleagues showed that information is maximized in an Ising scheme [77,78] at the critical temperature and that, beyond criticality, a law of marginal decreasing returns is attained [79]. These concepts have been expanded upon to more widely imply that critical systems are advantageous to evolution, since they are better at responding to their surroundings and guaranteeing their survival [80,81]. The Ising model is simple and applicable to numerous systems, including the integrated information theory (IIT).…”
Section: Connecting Biofield Resonance and Consciousnessmentioning
confidence: 99%
“…For instance, using data from the human connectome, Marinazzo and colleagues showed that information is maximized in an Ising scheme [77,78] at the critical temperature and that, beyond criticality, a law of marginal decreasing returns is attained [79]. These concepts have been expanded upon to more widely imply that critical systems are advantageous to evolution, since they are better at responding to their surroundings and guaranteeing their survival [80,81]. The Ising model is simple and applicable to numerous systems, including the integrated information theory (IIT).…”
Section: Connecting Biofield Resonance and Consciousnessmentioning
confidence: 99%